Peramalan Penjualan Pada Toko Retail Menggunakan Algoritma Backpropagation Neural Network - Musli Yanto; Eka Praja Wiyata Mandala; Dewi Eka Putri; Yuhandri Yuhandri (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
Retail is one or more activities that add value to the product to the consumer either for family needs or for personal use. Retail can sell products depending on current market needs. The goods we enjoy today are not apart from retail services, retail helps producers / distributors and consumers so that every need will be fulfilled. In this problem the author tries to do retail store research in the city of Padang. This research aims to help retail stores to forecast procurement of goods. Artificial Neural Network Backpropagation can make the forecasting process for procurement of goods for the next period of time on each item on the retail and will ultimately be useful for retail store managers. The forecasting process begins with determining the variables that will be required in the network pattern, then the pattern of established network will be continued on the network training process by using backpropagation algorithm. After doing the network training process the researchers will do a comparison with some pattern of network that has been formed. The last process undertaken in this research is the process of determining the best network pattern of the average value of errors obtained from each training network pattern. In the final result of the forecasting process, the results of the calculation have a total error of = 3.57%. Judging from the forecasting process that will be done not only used to predict the procurement of goods but also can predict sales figures in retail stores. In principle, this research can help to determine the procurement of goods in the sales process that will minimize the losses that occur in every sales activity.